1993
DOI: 10.2473/shigentosozai.109.337
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Copper from Motor Scrap Utilizing Ammonia Leaching Technique. Stuidies on the selective recovery of copper and iron from motor scrap. (2nd Report).

Abstract: To develop a hydrometallurgical process for the selective recovery of copper and iron from motor scrap. the leaching of copper with Cu (II). ammine solution using a spray-type or an up-stream penetration type reaction tank has been examined, and a closed circuit process has been proposed for the copper recovery. Copper can be leached by either spray leaching or up-stream penetration leaching with large leaching rate, where the resultant Cu (I) is oxidized to Cu (II) with air during the circulation of leachant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5][6] Majima et al reported the selective leaching of copper from motor scraps using cupric ammine solutions. 1,2) Zhou et al studied the removal of copper from ferrous scrap by an ammonia leaching method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Majima et al reported the selective leaching of copper from motor scraps using cupric ammine solutions. 1,2) Zhou et al studied the removal of copper from ferrous scrap by an ammonia leaching method.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Majima et al reported the selective leaching of copper from motor scraps using cupric ammine solutions. 1,2) Zhou et al studied the removal of copper from ferrous scrap by an ammonia leaching method. 3,4) In these studies, Cu(I) ions were obtained under an air or oxygen atmosphere as the reaction product, and then metallic copper would be electrowon from a sulfuric acid solution obtained by solvent extractionstripping.…”
Section: Introductionmentioning
confidence: 99%
“…PT-5050 is one of the Acorga products having the advantages of strong extraction, good stripping, and high selectivity for copper (Kirk-Othmer 1995;Majima et al 1993). Recovery of copper from hydrochloric acid solution and its transfer into H 2 SO 4 solution were reported using extractant mixtures such as trioctylamine-LIX 54 (Nigo et al 1993) and Alamine336-LIX 54 (Ritcey et al 1982;Kordosky 1992;Barakat and Mahmoud 1999).…”
Section: Overview Of Recovered Copper Values 137mentioning
confidence: 99%
“…Copper was recovered from a variety of solid wastes and other lean grade ores by ammonia leaching, solvent extraction with LIX 84, and electrowinning of metal from the stripped solution (Majima et al 1993;Nigo et al 1993). Ritcey et al (1982) studied the solvent extraction separation of copper and zinc from chloride liquors using Acorga P5300 for copper and TBP for zinc.…”
Section: Overview Of Recovered Copper Values 137mentioning
confidence: 99%
“…On the other hand, a hydrometallurgical process has certain advantages such that it could be economically operated even on a small scale and that the capital cost is lower than that for the conventional smelting process. So far, some efforts have been made to develop hydrometallurgical recycling processes; [1][2][3][4] these processes, however, have a problem in that power consumption during the copper electrowinning is relatively high. Thus, it is necessary to reduce the power consumption during the electrowinning to make the process economical and comparable to the low market price for copper.…”
Section: Introductionmentioning
confidence: 99%